Metabolite profiling and defense gene expression of susceptible and tolerant oil palm seedling progenies at early stage of Ganoderma boninense infection - Syd Ali, Nusaibah (2012)
Knowledge on the localized and systemic defense mechanism during Ganoderma boninense-oil palm interaction is of primary importance for detecting basal stem rot disease. Thus the objectives of this study include i) to establish and confirm G.boninense infection on oil palm root seedlings using artificial inoculation method, ii) to identify secondary metabolites accumulated in oil palm roots at early stages of G.boninense infection and assess their antifungal activities and iii) to profile expression of key genes for the biosynthesis of the identified compounds involved in defense mechanism. In this study, oil palm seedlings were artificially infected with G. boninense infested rubber wood blocks. Establishment of G. boninense infection at Mearly stages in tolerant and susceptible oil palm seedling progenies were examined through scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Metabolites present in oil palm roots during oil palm-G. boninense pathogenic interactions were investigated via gas chromatography-mass spectrometric (GC-MS) analysis. Antifungal assays were carried out to associate the involvements of total metabolites and single metabolite from inoculated oil palm roots extracts in defense mechanism against G. boninense infection. Gene expression analysis of anthranilate synthase α- subunit1 (EGASα-1) and stearoyl-ACP-desaturase3 (SAD3) genes from tryptophan and fatty acid pathways respectively were conducted with quantitative reverse transcriptase-polymerase chain reaction. A rapid outer layer colonization of hyphae was observed in the susceptible progeny compared to tolerant progeny through SEM. Cell wall degradation was observed through TEM as early as 24 hpi before penetration of G. boninense hyphae. Total metabolite in vitro study evaluating inhibitory activity of oil palm root methanolic against G. boninense showed that tolerant progeny extracts gave a higher inhibition rate with 100 % at 72 and 96 hpi, where else in susceptible extracts, 100% inhibition were only achieved at 96 hpi. An alkaloid metabolite, quinoline was found to have a much more rapid and elevated accumulation in the roots of tolerant progeny (56.4% at 72 hpi) compared to susceptible progeny (43.9% at 144 hpi) at early stages of G. boninense infection. Quinoline gave an EC50 of 0.211μg/ml and showed an increasing antifungal activity with increasing quinoline concentration against G. boninense. The level of EGASα-1 gene expression reached a maximum at 120 hpi in tolerant and susceptible progeny, whereby it was 3.0-fold and 1.5-fold higher respectively. Expression of SAD3 gene in infected roots was 5.3-fold and 1.7-fold in susceptible and tolerant progeny respectively at 120 hpi. This indicates SAD3 gene is constitutively expressed in oil palm roots and their expression levels were influenced by biotic stress. These findings showed that oil palm-G. boninense interaction induces biochemical defense and activates pathogenesis related genes as a form of early defense mechanism.